Myocarditis resulting from echo type 21 virus - Kanra, Güler; Dilmen, Uğur; Çağlar, Melda; Seçmeer, Gülten; Bilgiç, Arman; Günalp, Altan (The Turkish Journal of Pediatrics, 1983)
This is a case report of the clinical, pathological and virological investigations of a 5-month-old boy who was clinically and histopathologically diagnosed as having myocarditis caused by ECHO type 21 virus.